Robust yaw control of autonomous underwater vehicle based on fractional-order PID controller - Liu, Lu; Zhang, Lichuan; Pan, Guang; Zhang, Shuo (Ocean engineering, 2022)
Autonomous underwater vehicles (AUVs) have broad applications owing to their small size, low weight, strong ability to operate autonomously, and ability to replace humans in dangerous operations. AUV motion control systems can ensure stable operation in complex ocean environments and have attracted significant research attention in marine science and technology. The main difficulties with AUV motion control include the large uncertainties of dynamic and hydrodynamic characteristics and time delay of the signal transmission channel. In this study, we propose a robust fractional-order proportional–integral–derivative (FOPID) controller design for an AUV yaw control system. First, a three-dimensional stability region analysis method is proposed to achieve fractional orders. Unlike other stability region analysis methods, the proposed method is supported by theory instead of observation. Then, the other parameters are optimized according to the robust design specifications with respect to the parameter uncertainties. Therefore, the controlled system can tolerate different parameter uncertainties and fulfill transient performance specifications while maintaining system stability. The simulation results illustrate the superior robustness and transient performance of the proposed control algorithm. •A robust FOPID controller design method is presented for AUV yaw control system.•A three dimensional stability region analysis method is proposed to achieve the fractional orders.•The other parameters are optimized according to the robust design specifications.•The controlled system could tolerate different parameters uncertainties and fulfill design specifications.•Simulation results are given to illustrate the superior control performance of the proposed algorithm.